A l’origine des couleurs et éléments matériels d’œuvres peintes des XIVe-XVIe siècles - Anne-Solenn Le Hô; Sandra Montlouis; Sandrine Pagès-Camagna†; Nathalie Pingaud; Yannick Vandenberghe (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper is devoted to applied brocade, subject of the colloquium published here, and to others techniques of textile imitation such tin reliefs, sgraffito … encountred in painting and sculpture in the Middle Ages. An abstract of theses techniques is presented, and the methodology observed crossing observations and analysis describe the techniques and material features, the state of conservation, and the way to investigate the fragments often very lacunars. The Data providing from 55 sculptures have been compiled and confronted. They are dating from XIVth Century to XVIth Century, a very important period for the use of these ornaments ; they come from France, Germany, and Flanders. Cases Studies illustrate the techniques used in this corpus, studied at C2RMF by about thirty years.